The effects of competitive level and time of season on the use of imagery by Finnsih synchronized skaters - Arvinen-Barrow, M.; Weigand, D.; Hemmings, B.; Walley, M. (Journal of Sports Sciences, 2004)
Es wurde der Einsatz von Imagination unter finnischen Eiskunstläufern in Abhängigkeit vom Zeitpunkt in der Saison und dem Leistungsniveau der Athleten untersucht.